Evaluation of two laboratory model methods for diarrheal irritable bowel syndrome - Qian Chen; Hua Zhang; Chang-Yue Sun; Qing-Ying He; Rui-Rong Zhang; Bin-Fei Luo; Zi-Hao Zhou; Xiao-Fan Chen (BMC, 2023)
Abstract Background Diarrheal irritable bowel syndrome (IBS-D) is a common chronic functional gastrointestinal disorder, and the underlying pathogenic mechanism is still unclear. Animal models that mimic the pathological state of IBS-D patients were constructed to provide a reference for later drug research and model development. Methods The IBS-D model was induced using restraint stress and chemical stimulation (rhubarb), and rats were divided into normal control group (NC), chemically stimulated group (CS), and restraint stress group (RS). Visceral motility responses to Colorectal Balloon Dilation (CRD) were measured by Abdominal Withdrawal Reflex (AWR); evaluation of faecal properties and water content; determination of colonic tissue tight junction (TJ) mRNA expression by RT-PCR; measurement of inflammatory cytokines by ELISA; and intestinal flora and short chain fatty acids. Results Compared to NC group, CS and RS group rats showed increased intestinal sensitivity and Bristol stool score, significant diarrheal symptoms and weight loss. Mucin 2, ZO-1, OCLN, CLDN4 mRNA expression was reduced and the intestinal mucosal barrier function was diminished. In addition, the levels of inflammatory factors IL-1β, IL-6, IL-8, IL-10 and TNF-α increased, the abundance and diversity of intestinal flora decreased, the content of beneficial bacteria such as Bifidobacteria decreased, and SCFAs such as acetic acid, propionic acid and butyric acid decreased to different degrees. Although, no significant difference was observed for any molecular and inflammatory marker, but compared to CS group, RS group had less water in the stool, higher visceral sensitivity, and higher relative abundance of beneficial intestinal bacteria such as Actinobacteria. Conclusion In conclusion, restraint stress combined with chemical stimulation can mimic the pathological state of diarrhoea symptoms, visceral hypersensitivity, reduced intestinal mucosal barrier permeability, immune regulatory dysfunction and dysbiosis in IBS-D patients. However, herbs with antibacterial effects such as rhubarb and senna, for example, are not suitable as the first choice for chemical stimulation, as they may lead to a decrease in harmful bacteria and an increase in beneficial bacteria in the intestinal fraction and do not perfectly mimic the imbalanced state of intestinal flora in IBS-D patients, while restraint stress may be a key factor in modelling.